2018
DOI: 10.1186/s11671-018-2616-0
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Approach for the Preparation of Nano-size Zinc Oxide in Water/Glycerol with Extremely Concentrated Zinc Sources

Abstract: A facile process to prepare zinc oxide (ZnO) nanoparticles from an aqueous zinc chloride (ZnCl2) solution and an aqueous hydroxide solution under a glycerol stabilizer at room temperature was developed. ZnCl2 aqueous solutions as concentrated as 65–80 wt% were used as the concentrated zinc source. The concentration of ZnCl2 solutions and the molar ratio of glycerol to Zn2+ had obvious effects on the sizes and shapes of the ZnO nanoparticles. The shape of ZnO nanoparticles changed from rods approximately 50–120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 30 publications
2
21
1
2
Order By: Relevance
“…Various researchers [37,[39][40][41][42] suggested that Zn salt and/or NaOH concentrations play a crucial role in the obtained size, texture, and optical properties of ZnO nanostructures. The UV-Vis absorbance peaks of ZnO NPs prepared at various Zn salt to NaOH molar ratio )MZn:MNaOH) from 1:1 to 1:4 are depicted in Fig.…”
Section: Mzn:mnaoh)mentioning
confidence: 99%
“…Various researchers [37,[39][40][41][42] suggested that Zn salt and/or NaOH concentrations play a crucial role in the obtained size, texture, and optical properties of ZnO nanostructures. The UV-Vis absorbance peaks of ZnO NPs prepared at various Zn salt to NaOH molar ratio )MZn:MNaOH) from 1:1 to 1:4 are depicted in Fig.…”
Section: Mzn:mnaoh)mentioning
confidence: 99%
“…Furthermore, glycerol can act as a stabilizer of nanometric species, leading to the straightforward recycling of the catalytic phase (Chahdoura et al, 2014). The conventional and MW-assisted preparation of NPs in glycerol has already been described in the literature and this field of interest is continuously growing (Wang et al, 2018;Ghosh et al, 2019;Parveen et al, 2019;Vinodhini et al, 2019). CuNPs are an efficient source of Cu, but their potential applicability is restricted by copper's inherent instability under atmospheric conditions (Gawande et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It can be used to visualize inorganic, organic, carbon-based, biological, and complex materials as spherical and equiaxial particles, tubes, flakes, rods, or fibers. The size, size distribution, crystalline structures, and aggregates of ZnO NPs have been analyzed using TEM [46,118,119]. The TEM technique is extensively used to determine the size, size distribution, and morphology of ZnO NPs based on the stabilizer (glycerol)-to-zinc source ratios during the synthesis [46,109].…”
Section: Physicochemical Characterization and Toolsmentioning
confidence: 99%
“…The size, size distribution, crystalline structures, and aggregates of ZnO NPs have been analyzed using TEM [46,118,119]. The TEM technique is extensively used to determine the size, size distribution, and morphology of ZnO NPs based on the stabilizer (glycerol)-to-zinc source ratios during the synthesis [46,109]. Li et al [118] reported the layer-by-layer growth of ZnO nanopillar crystals using in situ, high-resolution TEM.…”
Section: Physicochemical Characterization and Toolsmentioning
confidence: 99%
See 1 more Smart Citation